Students’ Perception on Utilizing TikTok Videos for Vocabulary Acquisition - Abidah, Amelia Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The primary aim of this study is to uncover and comprehend students' perspectives on acquiring and using English language through the TikTok application. The study employed a descriptive qualitative research methodology to investigate the students' perspective of learning English vocabulary through the TikTok application and their attitudes toward the platform. In addition, this study employed an interview protocol with seven open-ended questions throughout the interview phase, involving a total of ten students. The findings indicate that the TikTok application provides users with various types of English vocabulary, such as daily vocabulary, idioms, and slang vocabulary. Additionally, the study explores both positive and negative perceptions of using TikTok for learning English vocabulary, as well as the benefits that students derive from using the platform. Based on the data, the majority of pupils acquire English vocabulary quickly by utilizing the TikTok program. Nevertheless, a drawback that students frequently mention as hindering their acquisition of new terminology is the distraction caused by applications. This research aims to make a valuable contribution to the effective utilization of technology, particularly social media, to enhance English vocabulary acquisition.